2018
DOI: 10.12701/yujm.2018.35.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in minimally invasive surgery for gynecologic indications

Abstract: Recently, an increasing interest in less invasive surgery has led to the advent of laparoendoscopic single-site surgery (LESS) and natural orifice transluminal endoscopic surgery (NOTES). LESS and NOTES could be technically challenging, but available literature has demonstrated the feasibility and safety of LESS for benign gynecologic diseases. However, the evidence is not strong enough to recommend the use of LESS over that of conventional multiport laparoscopic surgery (MLS). As per the results of the most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…[ 1 ] In no other field of medicine are the benefits of catheter‐based approaches more obvious than in cardiovascular disease treatment, where surgeries are accomplished quicker, with faster postoperative recovery times and improved clinical outcomes, compared to traditional sternotomy procedures. [ 1,2 ] However, catheter‐based interventions come with a major disadvantage, namely the required use of X‐ray or fluoroscopic imaging, which exposes the patients to harmful ionizing radiation and contrast agents. They are particularly harmful to use during the neonatal period, such as umbilical catheterization, which is typically required for preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] In no other field of medicine are the benefits of catheter‐based approaches more obvious than in cardiovascular disease treatment, where surgeries are accomplished quicker, with faster postoperative recovery times and improved clinical outcomes, compared to traditional sternotomy procedures. [ 1,2 ] However, catheter‐based interventions come with a major disadvantage, namely the required use of X‐ray or fluoroscopic imaging, which exposes the patients to harmful ionizing radiation and contrast agents. They are particularly harmful to use during the neonatal period, such as umbilical catheterization, which is typically required for preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy may require a higher level of surgical skill that adnexal surgery does; nevertheless, LESS is now widely applied for not only laparoscopic-assisted vaginal hysterectomy (LAVH) but also total laparoscopic hysterectomy (TLH) [ 5 , 6 , 7 ]. In 2015, a retrospective study reported that 80% of hysterectomies in a single hospital in Korea were performed via LESS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of learning curve, the most difficult procedure is vaginal cuff suture and proficiency can be achieved after 14 cases. In general, large uterus and previous abdominal surgery are considered limitations of R-LESS hysterectomy and may require a longer learning curve [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the implementation of 5mm-mini-incision LESS has higher requirements. It is better to be prepared fully and well-trained to reduce the risk of surgery effectively and ensure the success of the operation [15].…”
Section: Discussionmentioning
confidence: 99%